Quantitative Analysis of Secondary Metabolites and Solvent Optimization of Secang Wood Extract (Caesalpinia Sappan L/BiancaeaSappan) as Disclosing Agent - Naning Kisworo Utami; Metty Amperawati; Muhammad Ikhwan Rizki (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2022)
Disclosing solution is a material that is often used to see the presence of plaque, made of erythrosine base material. Erythrosine is one of the food coloring ingredients and can also be used for bacterial staining, can cause allergic reactions and this dye also has the potential as a carcinogen. The purpose of the study is to figure 1). qualitative of the secondary metabolites of brazilin compounds in secang wood extract, 2). quantitative of the secondary metabolites of brazilin compounds in secang wood extracts and 3). toxicity in secang wood extract using the BSLT shrimp larva toxicity test (Brine Shrimp Lethality Test). The study design is a non-experimental one that will examine quantitatively on secondary metabolites of secang wood extract and toxicity tests. The research tools used are ovens, grinders, mechanical sieves, maceration vessels, hydraulic presses, rotary evaporators, water baths, Uv-Vis spectrophotometers, glass tools and materials used are secang wood and other materials used namely ethanol pro analysis, methanol pro analysis, hexane pro analysis, ethyl acetate pro analysis, aqua sterile, what man paper, FeCl3, HCl, shrimp larvae, and larval growing media. Quantitative analysis test obtained the level of secang wood brazilin which is 8.54% b / b. In toxicity tests using Uv-Vis spectrophotometers, the results of wood extracts are not toxic to living things based on toxicity tests with shrimp larva test models. Conclusion, secang wood contains brazilin which plays a role in giving red color and is not toxic to living creatures so that it is safe to use in humans.